Glucose but Not Fructose Alters the Intestinal Paracellular Permeability in Association With Gut Inflammation and Dysbiosis in Mice - Zhang, Xufei; Monnoye, Magali; Mariadassou, Mahendra; Beguet-Crespel, Fabienne; Lapaque, Nicolas; Heberden, Christine; Douard, Veronique (Frontiers in Immunology, 2021)
A causal correlation between the metabolic disorders associated with sugar intake and disruption of the gastrointestinal (GI) homeostasis has been suggested, but the underlying mechanisms remain unclear. To unravel these mechanisms, we investigated the effect of physiological amounts of fructose and glucose on barrier functions and inflammatory status in various regions of the GI tract and on the caecal microbiota composition. C57BL/6 mice were fed chow diet and given 15% glucose or 15% fructose in drinking-water for 9wks. We monitored caloric intake, body weight, glucose intolerance and adiposity. The intestinal paracellular permeability, cytokine and tight junction protein expression were assessed in the jejunum, caecum and colon. In the caecum, the microbiota composition was determined. Glucose-fed mice developed a marked increase in total adiposity, glucose intolerance, paracellular permeability in the jejunum and caecum while fructose absorption did not affect any of these parameters. Fructose-fed mice displayed increased circulation levels of IL6. In the caecum, both glucose and fructose intake were associated with an increase in Il13, Ifn and Tnf mRNA and MLCK protein levels. To clarify the relationships between monosaccharides and barrier function, we measured the permeability of Caco-2 cell monolayers in response to IFN+TNF in presence of glucose or fructose. In vitro, IFN+TNF-induced intestinal permeability increase is less pronounced in response to fructose than glucose. Mice treated with glucose showed an enrichment of Lachnospiracae and Desulfovibrionacae while the fructose increased relative abundance of Lactobacillaceae. Correlations between pro-inflammatory cytokine gene expression and bacterial abundance highlighted the potential role of members of Desulfovibrio and Lachnospiraceae NK4A136 group genera in the inflammation observed in response to glucose intake. The increase in intestinal inflammation and circulating levels of IL6 in response to fructose were observed in absence of intestinal permeability modification, suggesting that the intestinal permeability alteration does not precede the onset of metabolic outcome (low-grade inflammation, hyperglycemia) associated with chronic fructose consumption. The data also highlight the deleterious effects of glucose on gut barrier function along the GI tract and suggest that Desulfovibrionaceae and Lachnospiraceae play a key role in the onset of GI inflammation in response to glucose.